1976
DOI: 10.1002/app.1976.070200917
|View full text |Cite
|
Sign up to set email alerts
|

Electron spectroscopy for chemical analyses (ESCA)—A tool for studying treated textiles

Abstract: SynopsisElectron spectroscopy for chemical analysis (ESCA) has been successfully used to determine the location of flame-retardant polymers or reagents and crosslinking and oil/water-repellent reagents in relation to fiber surfaces of chemically modified cotton fabrics and cotton/polyester blends. Changes in intensity of characteristic ESCA element signals were followed as the particle size of the treated fabric varied. Dimethyloldihydroxyethyleneurea (DMDHEU) and the flame-retardant polymer formed from tetrak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Other wet chemical methods that have been proposed to monitor the fibre bulk easy care finish concentration are based on Kjedahl analysis of nitrogen content (Ibrahim et al 2008;Soignet et al 1976), titrimetry (Xu and Shyr 2001) and Leuco HCN Analysis (Hashem et al 2003). FTIR has also been used to probe the nature and concentration of easy care cross-linkers (Yang 2001;Li et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other wet chemical methods that have been proposed to monitor the fibre bulk easy care finish concentration are based on Kjedahl analysis of nitrogen content (Ibrahim et al 2008;Soignet et al 1976), titrimetry (Xu and Shyr 2001) and Leuco HCN Analysis (Hashem et al 2003). FTIR has also been used to probe the nature and concentration of easy care cross-linkers (Yang 2001;Li et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of cellulosic materials X-ray photoelectron spectroscopy (XPS) has been used in establishing the distribution and concentration of non-cellulosic materials (Mitchell et al 2005;Buchert et al 2001;Johansson et al 1999) and in assessing the effectiveness of fibre surface modification in order to impart product enhancement for both (Carty and Byrne 1987) cellulosic and non-cellulosic fibres (Xu and Shyr 2001;Battistel et al 2001;Benerito et al 1981;Shekarriz et al 2003). While XPS has previously revealed an even distribution of DMDHEU throughout the cotton fabric (Soignet et al 1976), oil and water repellent finishes are reported to be deposited on the cotton fabric surface only (Soignet et al 1976;Benerito et al 1981). XPS has also been used to assess the wash durability of non-formaldehyde and water repellency finishes by probing the F/O ratio (McCord et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…XPS is commonly used in surface chemical analysis of textile substrates. For instance XPS was used to determine the location of the flame retardants, soil repellence and easy care finishes following application of the finishes on the cotton fabrics and the results indicated that in order to understand the effectiveness of the appli-cation of the finishes, it is necessary to determine both surface and bulk analysis of the treated fabrics due to the fact that some of the finishes reacts in both the surface and bulk of the substrates [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, electron spectroscopy for chemical analysis (ESCA) , also referred to as Xray photoelectron spectroscopy (XPS) , a nondestructive solid-state spectroscopic technique that has already been employed in the analysis of surfaces of synthetic polymer^,^-^ natural and textile fibers, [7][8][9][10][11][12] and in the characterization of wood reactions, 13,14 was used to investigate the nature of wood-periodic acid intermediates in situ and in an attempt to elu-cidate the nature of chemical reactions occurring between periodic acid and the constituents of wood. This article, the first of a series, presents results from ESCA analysis of untreated and treated woods.…”
Section: Introductionmentioning
confidence: 99%